Empirical Tests of relation between liquidity and expected return: Evidence from UK - Li, Yuan (2009)
This paper provides the empirical tests of liquidity premium by using two approaches of cross-sectional regression and portfolio analysis based on 550 common stocks randomly collected from LSE (London Stock Exchange) over the sample period of 1993 to 2008. The proxies for liquidity employed in this study are BA12 and TO12 both of which are adjustment to commonly used liquidity measures and both firm size and book-to-market are under control. The evidence suggests the positive size effect and negative value effect on expected stock return which are not consistent with several previous researches such as Datar et al. (1998). In addition, the positive predictive power of BA12 for expected stock return is not independent of market capitalization and negative predictive power of TO12 is not significant in this study. Thus, the liquidity premium is not observed depending on existing sample and sample period and it needs more obvious and strong empirical evidence to confirm.